1992
DOI: 10.1016/0378-1097(92)90351-n
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of a red form of methanol dehydrogenase from the marine methylotroph Methylophaga marina

Abstract: The quinoprotein methanol dehydrogenase (MDH) of the marine methylotroph Methylophaga marina is similar to that of other methylotrophs in being an α2β2 tetramer containing two molecules of PQQ and a single atom of calcium. Its electron acceptor is cytochrome cL and interaction of the two proteins is by way of carboxylates on the cytochrome and lysyl residues on the α subunit of MDH. The reaction was not, however, sensitive to high ionic strength as was the reaction in non‐halophilic bacteria. A red form of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Phylogenetic affiliation to cultured organisms showed that 16% of total clones can be related to cultured sulfur-metabolizing strains, about half of them appeared to be involved in sulfur reduction (Vogt et al 2008), 30% in sulfur-oxidation (Inagaki et al 2003), 20% in sulfite-oxidation (Ivanova et al 2004) and 5% in sulfide-oxidation (Wirsen et al 2002). Two of our clones are most closely related to methylotrophic bacteria (Chan and Anthony 2006).…”
Section: Molecular Phylogenymentioning
confidence: 90%
“…Phylogenetic affiliation to cultured organisms showed that 16% of total clones can be related to cultured sulfur-metabolizing strains, about half of them appeared to be involved in sulfur reduction (Vogt et al 2008), 30% in sulfur-oxidation (Inagaki et al 2003), 20% in sulfite-oxidation (Ivanova et al 2004) and 5% in sulfide-oxidation (Wirsen et al 2002). Two of our clones are most closely related to methylotrophic bacteria (Chan and Anthony 2006).…”
Section: Molecular Phylogenymentioning
confidence: 90%
“…Originally, the enzyme was thought not to contain any metal atoms (Anthony and Zatman, 1967). More recently, atomic-absorption spectroscopy revealed the presence of tightly bound Ca2l in MEDHs from P. denitrificans, Methylobacterium extorquens, Methylophilus methylotrophus, Hyphomicrobium X (Richardson and Anthony, 1992), Methylobacterium glycogenes (Adachi et al, 1990a) and Methylophaga marina (Chan and Anthony, 1992). On the basis of the belief that MEDH possessed one atom of Ca2", Richardson and Anthony (1992) proposed a model in which a single Ca21 interacting with both a. subunits influenced the configuration of the two active sites.…”
Section: Introductionmentioning
confidence: 99%